Integrating Risk Management Frameworks: Practical Steps to Mitigate Inherent Risks - Simbolon, Novi Handayani; Jati, Fatma Dwi; Siahaan, Sondang Beatrix (Jurnal Akuntansi, Keuangan dan Perpajakan, 2024)
Banking activities are currently growing very rapidly, both in the external environment and the internal banking environment. All of these activities meet with an uncertainty related to the probability of these activities being carried out successfully according to plan or not, so that various kinds of risks arise. The wider range of banking business activities will also be followed by the increasingly complex risks in banking activities. This research aims to analyze the implementation  of risk management to avoid or reduce the impact caused if the risk occurs through qualitative analysis. Descriptive qualitative research aims to describe the application of risk management to mitigate these risks in detail and in depth, so as to obtain an understanding of the context, meaning, and characteristics of the results of the analysis by collecting and analyzing data descriptively. Descriptive qualitative research focuses on an in-depth understanding of a problem without trying to test hypotheses or measure variables quantitatively.